Does the Eighth Amendment Punishments Clause Prohibit Only Punishments That Are Both Cruel and Unusual? - Meghan J. Ryan (Washington University Law Review, 2010)
There is a great struggle in the United States between proponents of the death penalty and death penalty abolitionists who believe that the practice is cruel and even unconstitutional. Although the punishment of death is enshrined in the Fifth and Fourteenth Amendments of the Constitution, the Supreme Court seems to have followed its moral compass in chipping away at the death penalty because of the cruelty of the practice. The Court's struggle between the text of the Constitution and its moral inclinations in the death penalty context has resulted in an inconsistent and confusing Eighth Amendment Punishments Clause jurisprudence. While attempting to maintain neutrality on the topic and thus relying almost exclusively on assessing the unusualness of a practice through a purportedly objective assessment of state legislative action, the Court seems to have covertly injected into the equation its subjective views as to what punishments are unconstitutionally cruel. This tension between an objective measure of unusualness and a subjective assessment of cruelty has led the Court to make inconsistent statements about whether the Punishments Clause prohibits only punishments that are both cruel and unusual, or rather prohibits both cruel punishments and unusual punishments. This Article goes where no other has, identifying and exploring this important question. After tracing the history of the Eighth Amendment, analyzing the Court's early interpretations of the prohibition on “cruel and unusual punishments,” and parsing the text of the Punishments Clause, the Article concludes that the Clause prohibits only punishments that are both cruel and unusual and that each of these components of the Clause should thus be independently assessed. While this interpretation may narrow the scope of the Amendment, it allows for further innovations in humane methods of punishment and revives the federalist foundation of this nation that the Court's current jurisprudence has stifled.
Keywords: Cruel & amp; unusual punishment; Eighth amendment protections (United States Constitution); Capital punishment; United States. Supreme Court